COMBINED METHOD OF BULK MATERIAL SHIELDING EVALUATION FOR 200 MEV HIGH ENERGY NEUTRON SOURCE USING PHITS MODELLING AND PARTIAL DENSITY - Aliyah, Fitrotun; Rahman, Azhar Abdul; Md Radzi, Yasmin; Kambali, Imam (Program Studi Fisika Universitas Negeri Jakarta, 2023)
Neutron encounters difficulties in shielding protection. Thus, many researchers have performed simulation and experimental research on neutron shielding materials. The characteristic of materials is highly dependent on neutron energy. The evaluation of neutron shielding for various materials, such as iron, concrete, aluminum, and borated polyethylene (BPE), was conducted in this paper through simulation using a Monte Carlo code of PHITS 3.27 and calculation via partial density method. A mono-energetic neutron source with an energy of 200 MeV is emitted perpendicular to the shielding material with a thickness of 105 cm. The parameters measured in this analysis include flux, fast neutron removal cross-section, neutron depth dose, ambient dose H*(10) equivalent, and neutron dose reduction factor (RF). Results show that iron is a good material against high-energy neutron and secondary photon radiation at the energy range with the highest removal cross-section and the lowest RF value (0.39), followed by concrete, BPE, and aluminum. The integrated fluence and effective dose profiles were consistent with previous results in the literature. Benchmarking calculation of neutron dose RF was conducted with other publications and was in good agreement within the value range.